EFISIENSI PEMUPUKAN P TANAMAN CABE PADA LAHAN INTENSIFIKASI YANG DIBERI BAHAN ORGANIK DENGAN TEKNIK P-32 - Yulnafatmawita Yulnafatmawita; Lusi Maira; Junaidi Junaidi; Yusmini Yusmini; Nurhajati Hakim (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2006)
Phosphorous (P) is one of plant nutrient needed by plant in much amount as it is called as macro essential plant nutrient. This element, P, has complete problems. It is not only found in a small amount in soil compared to other nutrients, but it also has some problems in soil if it is there. At acid soils such as Ultisols, phosphorous is binded by aluminium (Al) and iron (Fe), while in basic soils it is held by calcium (ca) and magnesium (Mg). Therefore, both in acid soils or basic soils P is not available for plant growth. A research about P-fertilizer use efficiency for chilli (Capsicum annum) on intensification land which was added organic matter (OM) using P-32 technique was conducted in glasshouse and soil laboratory of Agricultural Faculty, and in laboratory of center for research utilizing nuclear science and technique (P3IN) Andalas University Limau Manis Padang from 1996 to 1997. The objective of this research was to measure P-fertilizer use efficiency (FUE) by chili on horticulture intensification area (on Andisols) as affected by organic matter. This research was designed as completely randomized design (CRD) with 2 factors those were TSP (consisting of 0, 25, and 50 kg P2O5/ha) and OM especially chicken manure (consisting of 2, 4, 6, 8, and 10 ton/ha) by 3 replications. The results showed that plant dry matter became higher by decreasing P-fertilizer added but was not significantly affected by manure. P-fertilizer (P-32) uptake by plants was not significantly affected by P-fertilizer and manure aapplication, therefore P-FUE decreased by increasing P-fertilizer added and tended to increase by increasing dosage of manure applied. Key words: fixed-P, available-P, desorpted-P, FUE, P-32 technique